Assessment of Incidence and Risk Factors of Hematoma Formation at Femoral Access Site among Saudi Patients post Cardiac Catheterization - Lama Bader Mofareh Alanazi; Saad Abdulrhman Almoqari; Huran Sarhan Othman Alotaibi; Faisal Hamad Eid Alotaibi; Yousef Khudhayr Sunaytan Alotaibi; Abdullah Sulaiman Theyab Alotaibi; Fawaz Break Nagaa Alotaibi; Gays Obaid Salah Al Otaibi; Abdullah Abdulrahman Alquwiz; Ibrahim Awadh Alziadi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Hematoma formation at the femoral access site is a mutual and possibly severe complication of invasive cardiovascular procedures. Aims: To assess the incidence and risk factors of hematoma formation atfemoral access site among Saudi patients post cardiac catheterization. Design: Descriptive research design was used. Subject and setting: All available adult patients (200), aged 18-65 years old, from both sexes who were attend to cardiac Catheterization unit at Makkah Hospital for a diagnostic procedures or interventional cardiac catheterization within 6 months’ period. Tools: two tools were used (I) Patient interview questionnaire, and (II) risk factors assessment list. Results: Incidence of femoral access hematoma formation over six months was (20%) percentage. Regarding medical data more than half of the studied patients had hypertension (61.5%), majority had a history of previous hospitalization (84.0%), large portion of them performed cardiac catheterization for diagnostic purposes and were smokers (39.0%). Regarding the modifiable risk factors, obesity was the 29(14.5%), position change during compression 31(15.5%), Number of artery puncture (25 %) Renal dysfunction 19(9.5%), Early ambulation 27(13.5), Use of anticoagulant 17(8.5%). Regarding the non-modifiable risk factors were found among 29(14.5%) of the studied patients who were advanced in age 29(14.5%) andmale gender was 27(13%) While, the non-modifiable risk factors were 14.5 1.5 and 9.5% including advanced age and hypertension among male patients. Conclusion: There was A hematoma formation among patients after cardiac catheterization There were correlation between medical data, modifiable risk factors & non-modifiable risk factors. Recommendations: Developing a standardizing protocol about hemostasis, sheath removal for providing education and training to healthcare providers to identify and manage such risk factors.